Portraying the Multitudes: Representation of Identities of Sexual Minorities on Indonesia-Based Feminist Web Magazine Magdalene.co - Puji Maharani (Jember University Press, 2018)
Abstract This paper aims to interrogate the representation of identities of sexual minorities, also known as LGBTQ (Lesbian, Gay, Bisexual, Trans, Queer), on Magdalene.co, an Indonesia-based feminist web magazine which provides a slanted guide to women and issues and offers and engages with fresh perspectives beyond traditional gender and cultural confines. The representation of sexual minorities is observed through a selection of six published articles written by editorial members and from contributors’ submissions, varying in age, gender, self-identification as sexual minorities, and degree of anonymity. The articles are analysed via discourse analysis, primarily based on discourse theory by Ernesto Laclau and Chantal Mouffe. Also, incorporated into the analysis are Adrienne Rich’s theory of politics of location to look at bodies of sexual minorities, and Gilbert Herdt’s(2009) concept of sexual panic to look at the increasing religious-conservatism in Indonesia in contrast to the sexuality of sexual minorities. Through this research, I aim to examine the ways in which the representation of sexual minorities in the media opens a space of resistance against heteronormative public discourse.